Collaborative Governance in the Optimization of Tax Revenue: Case Study in Yogyakarta - Arsandi, Sanda (Research and Development Agency Ministry of Home Affairs, 2022)
Yogyakarta Regional Tax Office always has difficulty satisfying tax revenue targets year by year. For example, Yogyakarta’s DGT could not meet the revenue target in the last three years, while DGCE always exceeded the target. Reflecting on this condition, Yogyakarta Regional Tax Office needs help from other agencies in the form of collaborative governance that might help them achieve the set targets. Meanwhile, there is a lot of research on Collaborative Governance, but robust generalizations to link theory and practice are still being sought. In order to complement between theory and practice of collaboration, this study discusses the implementation of Collaborative Governance for optimizing state revenues by conducting case studies at the Directorate General of Taxes (DGT) and the Directorate General of Customs and Excise (DGCE) in Yogyakarta. The qualitative method was used with data acquisition through interviews and literature studies. Based on the results, it was found that Collaborative Governance in Yogyakarta is following the Emerson, Nabatchi, and Balogh framework (2012) since it has several system contexts and strong drivers. Resource Conditions and Socio-Economic Conditions are the system context behind the collaboration between the two agencies. Meanwhile, Leadership, Dependence, and Uncertainty are the drivers that trigger Collaborative Governance. Furthermore, by using data matching, the researcher identified the potency of tax revenue from the bonded zone that could be elaborated in Yogyakarta. Finally, we identified several obstacles and challenges to implementing Collaborative Governance in Yogyakarta and formulated practical and theoretical recommendations for them.